Recent Progress in 3D Printing of Smart Structures: Classification, Challenges, and Trends - Yuyang Ji; Congcong Luan; Xinhua Yao; Jianzhong Fu; Yong He (Advanced Intelligent Systems, 2021)
Recently, considerable achievements have been made with the advancements of smart structures, which are known for their controlled deformation, self‐repair, and sensing characteristics. Such capabilities have significant potential in the field of bionics. 3D printing methods have revolutionized the high‐resolution integrated manufacturing of complex smart structures, resulting in new types of soft robots, actuators, wearable flexible electronics, and biomedical equipment. There is therefore a need for academia and industry to receive an update on the status of these tools. For this reason, herein, a comprehensive overview of the latest progress in printing methods, materials, and applications of various smart structures is provided. Temperature‐ and electromagnetic‐responsive smart structures are highlighted, in addition to self‐healing and smart‐sensing devices. Current exigencies and future development trends of 3D printing methods and smart structures are also summarized.